Dependence of macrophage superoxide release on the pulse amplitude of an applied pressure regime: a potential factor at the soft tissue–implant interface. (24th July 2013) - Shin, Hainsworth Y.; Frechette, Danielle M.; Rohner, Nathan; Zhang, Xiaoyan; Puleo, David A.; Bjursten, Lars M.
Abstract: Failure of soft tissue implants has been largely attributed to the influence of biomaterial surface properties on the foreign body response, but some implant complications, e.g. macrophage accumulation and necrosis, are still not effectively addressed with surface treatments to minimize deleterious biomaterial effects. We explored an alternative explanation for implant failure, linking biocompatibility with implant micromotion‐induced pressure fluctuations at the tissue–biomaterial interface. For this purpose, we used a custom in vitro system to characterize the effects of pressure fluctuations on the activity of macrophages, the predominant cells at a healing implant site. Initially, we quantified superoxide production by HL60‐derived macrophage‐like cells under several different pressure regimes with means of 5–40 mmHg, amplitudes of 0–15 mmHg and frequencies of 0–1.5 Hz. All pressure regimes tested elicited significantly ( p < 0.05) reduced superoxide production by macrophage‐like cells relative to parallel controls. Notably, pressure‐sensitive reductions in superoxide release correlated ( r 2 = 0.74; p < 0.01) only with pulse pressures. Based on the connection between superoxide production and cell viability, we also explored the influence of cyclic pressure on macrophage numbers and death. Compared to controls, adherent macrophage‐like cells exposed to 7.5/2.5 mmHg cyclic pressures for 6 h exhibited significantly ( p < 0.01) reduced cell numbers, independent of cell death. A similar effect was observed for cells treated with 10 U/ml superoxide dismutase. Collectively, our results suggest that pressure pulses are a putative regulator of macrophage adhesion via a superoxide‐related effect. Pressure fluctuations, e.g. due to implant micromotion, may, therefore, potentially modulate macrophage‐dependent wound healing. Copyright © 2013 John Wiley & Sons, Ltd.